A new software program for monitoring the energy distribution in a thermal waste treatment plant system. (January 2022) - Trojan, Marcin; Taler, Jan; Smaza, Krzysztof; Wróbel, Wojciech; Dzierwa, Piotr; Taler, Dawid; Kaczmarski, Karol
Abstract: The paper presents a novel system for monitoring the operation of a thermal waste treatment plant. The computer program is based on measurements of pressure, temperature, and mass flow rate of the working medium. The boiler efficiency is calculated using an indirect method. Thermal online calculations of the boiler combustion chamber make it possible to determine the heat flow rate to the evaporator. Based on the energy balance of the boiler evaporator, the superheated steam mass flow rate is determined, taking into account the mass flow rates of water injected into steam attemperators. By comparing the calculated and measured value of steam mass flow rate, the calorific value of the fuel fed is determined. The developed system enables monitoring of energy flow rates in individual elements of the power unit, taking into account losses in the boiler and turbine condenser. The following parameters are determined online, the efficiency of the boiler and the entire incinerator, heat losses in the boiler and the turbine condenser, as well as the heat flow rate, supplied to the municipal district heating system. By monitoring the plant operation, it is possible to adjust online the optimum excess air ratio. Highlights: A mathematical model of the boiler in a waste incinerator plant was presented. A mathematical model of the entire thermal waste treatment plant was presented. Results of the boiler monitoring were presented. Results of the entire thermal waste treatment plant operation were presented.